Pengaruh Iklan Televisi terhadap Pengambilan Keputusan Pembelian Konsumen Es Krim Magnum - Fikhi Nayatul Azmi; Ma'mun Sarma (Jurnal Manajemen dan Organisasi, 2017)
According to Nielsen Advertising Information Services said the 2015 total advertising expenditure increased by 4%. This increase was also influenced by existing companies in Indonesia including PT Unilever Indonesia. Tbk with its brand advertising products Wall's Magnum Ice Cream. This study aims to identify consumer ratings of advertising done by Ice cream Magnum, analyzing the effectiveness of ads Magnum Ice Cream is able to communicate the message and analyzing consumer purchase decisions over the ads that do Magnum Ice Cream. Data processing was performed using Statistical Package For Social Science (SPSS) 19 and Minitab 14. The analysis tool used is the EPIC model and Consumer Decision Model (CDM). Based on the analysis, the measurement response television advertising and communication impact that occurs, television commercials advertising the Magnum Ice Cream edition Taste the Classic included in the category of advertising is quite effective and have an impact until the real purchase.